Asymmetries of the Lower Limb: The Calculation Conundrum in Strength Training and Conditioning. Issue 6 (December 2016) - Bishop, Chris; Read, Paul; Chavda, Shyam; Turner, Anthony
ABSTRACT: ASYMMETRY DETECTION HAS BEEN A TOPIC OF INTEREST IN THE STRENGTH AND CONDITIONING (SC) LITERATURE WITH NUMEROUS STUDIES PROPOSING MANY DIFFERENT EQUATIONS FOR CALCULATING BETWEEN-LIMB DIFFERENCES. HOWEVER, THERE DOES NOT SEEM TO BE A CLEAR DELINEATION AS TO WHICH EQUATION SHOULD BE USED WHEN QUANTIFYING ASYMMETRIES. CONSEQUENTLY, THE AUTHORS HAVE UNCOVERED 9 DIFFERENT EQUATIONS THAT POSE CONFUSION AS TO WHICH METHOD THE SC SPECIALIST SHOULD USE DURING DATA INTERPRETATION. THE AIM OF THIS ARTICLE IS TO IDENTIFY THE DIFFERENT EQUATIONS CURRENTLY BEING USED TO CALCULATE ASYMMETRIES AND OFFER PRACTITIONERS A GUIDE AS TO WHICH METHOD MAY BE MOST APPROPRIATE WHEN MEASURING ASYMMETRIES.